At your 'online' service!: A continuous service-learning program for college students during the COVID-19 pandemic - Vicente, Niku E. (Animo Repository, 2021)
School health protocols in conducting face-to-face classes must be planned carefully to ensure that students will be safe from the effects of COVID-19. This is what the authors emphasized in a recent correspondence, which we re-echo in this paper in case the situation permits. However, a greater consideration must be given to colleges and universities where the aspect of community/social engagement of the students is already part of the curriculum. There is still a greater risk for students to go to the communities for service and social interaction. With this, we suggest that the service program can still continue through an enhanced electronic service-learning, which maximizes the human resources’ capacity and highlights students’ creativity with equally useful projects.